Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

solve in systems by substitution y=2x+1 and 2x-y=3

Sagot :

Answer: No Solution

Step-by-step explanation:

y=2x+1 and 2x-y=3

Substitute y=2x+1 into 2x-y=3

So you will have: 2x-2x+1=3

Then,

2x-2x=0

0+1=3

1=3

1 doesn't equal 3 so there is no solution.

Answer:

No solution.

Step-by-step explanation:

Notice that the second equation can be rearranged to be y = 2x - 3. 2x + 1 cannot equal 2x - 3 so there is no solution to this system.

We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.